2016
DOI: 10.1111/vop.12446
|View full text |Cite
|
Sign up to set email alerts
|

Transpalpebral exenteration in cattle: a retrospective study of 115 cases

Abstract: Early clinical diagnosis of SCC by owners and veterinarians may prevent the need for exenteration. Owners should be made aware of the possible postsurgical complications following exenteration in cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Previous retrospective studies performed in the United States reported more than 80 % of cattle that underwent enucleation or exenteration were diagnosed with OSSC. 3,9 Instead, more than half of the cattle population (55,3 %) of the present study was diagnosed with non-neoplastic ocular lesions, represented mainly by severe trauma with loss of globe content. A possible explanation for this difference could be the absence of Hereford cattle, known as being predisposed to OSCC development, 1 in our study population compared to the above-mentioned reports.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Previous retrospective studies performed in the United States reported more than 80 % of cattle that underwent enucleation or exenteration were diagnosed with OSSC. 3,9 Instead, more than half of the cattle population (55,3 %) of the present study was diagnosed with non-neoplastic ocular lesions, represented mainly by severe trauma with loss of globe content. A possible explanation for this difference could be the absence of Hereford cattle, known as being predisposed to OSCC development, 1 in our study population compared to the above-mentioned reports.…”
Section: Discussionmentioning
confidence: 73%
“…Performing enucleation or exenteration under sedation and local anesthesia may significantly decrease the risks associated with general anesthesia, including regurgitation of ruminal content and occurrence of myopathies and neuropathies, as testified by other reports. 3,9 Despite the high proportion, none of the perioperative complications encountered in this study was considered life-threatening and none of the hemorrhages required blood transfusion.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…No globesparing orbital exploratory procedures have been described in ruminants, where exenteration is more commonly used particularly when vision has been lost and restoration of patient comfort is paramount. 3,14,15,29,30 To the authors' knowledge, this is the first documented case report of a mixed bacterial retrobulbar abscess with intraocular extension in a goat, with advanced imaging and subsequent surgical management.…”
Section: Discussionmentioning
confidence: 94%